A Conceptual Framework for Personal Science - Wolf, Gary Isaac; De Groot, Martijn (Frontiers in Computer Science, 2020)
This paper introduces a conceptual framework to guide research and education into the practice of personal science, which we define as using empirical methods to pursue personal health questions. Personal science consists of five activities: questioning, designing, observing, reasoning, and discovering. These activities are conceptual abstractions derived from review of self-tracking practices in the Quantified Self community. These practices have been enabled by digital tools to collect personal real-world data. Similarities and differences between personal science, citizen science and single subject (N-of-1) research in medicine are described. Finally, barriers that constrain widespread adoption of personal science and limit the potential benefits to individual wellbeing and clinical and public health discovery are briefly discussed, with perspectives for overcoming these barriers.